Penguatan Sikap Spiritual Siswa Melalui Kegiatan Kokurikuler dan Ekstrakurikuler di SMK Manbail Futuh Jenu Tuban - Siti Nurjanah; Ahmad Syaif; Nafaisal Ulumi; Dina Kamila (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2024)
Abstract: This research examines the implementation of strengthening students' spiritual attitudes through religious co-curricular and extra-curricular activities at SMK Manbail Futuh Jenu, Tuban. This research is a case study with data collection including interviews with the school principal, head of student affairs, PAI teachers, and students. And supported by observation of activities and documentation of activities. The data is then reduced, presented, and conclusions drawn. The results of the research show that strengthening students' spiritual attitudes through co-curricular and extra-curricular activities can be carried out well by internalizing spiritual values in every activity, both co-curricular and extra-curricular, in the form of getting used to prayer and worship in religious activities, mushofahah and tafakur traditions. Research data illustrates the fulfillment of several indicators. First, pray before and after carrying out activities. Second, students carry out worship according to their religion and beliefs. Third, students say greetings at the beginning and end of the activity. Fourth, students are grateful for the blessings and grace of Almighty God. Fifth, students make efforts in every endeavor and surrender. The six students protect the environment around the school. Seventh, students maintain relationships with fellow creatures of God. And eighth, Respect other people who carry out their own worship. This is in accordance with the aswaja an-nahdliyah values taught at Manbail Futuh Vocational School. Future researchers can continue their studies on measuring students' spiritual attitudes quantitatively so that they will complete the data on students' spiritual attitudes at SMK Manbail Futuh Jenu Tuban. Keywords: Extracurricular, Co-curricular, Spiritual Attitude Abstract: Penelitian ini mengkaji pelaksanaan penguatan sikap spiritual siswa melalui kegiatan kokurikuler dan ekstrakurikuler keagamaan di SMK Manbail Futuh Jenu Tuban. Penelitian ini merupakan studi kasus dengan pengumpulan data meliputi wawancara dengan kepala sekolah, waka kesiswaan, guru PAI, dan siswa. Serta didukung dengan observasi kegiatan dan dokumentasi kegiatan. Data kemudian direduksi, disajikan, dan ditarik kesimpulan. Hasil penelitian menunjukkan bahwa penguatan sikap spiritual siswa melalui kegiatan kokurikuler dan ektrakurikuler dapat terlaksana dengan baik dengan cara internalisasi nilai-nilai sprititual pada setiap kegiatan baik kokurikuler maupun ektrakurikuler, berupa pembiasaan doa dan ibadah dalam kegiatan keagamaan, Tradisi mushofahah dan tafakur. Data penelitian menggambarkan terpenuhinya beberapa indikator. Pertama, berdoa sebelum dan sesudah melaksanakan kegiatan. Kedua, siswa menjalankan ibadah sesuai agama dan kepercayaan yang dianut. Ketiga, siswa mengucapkan salam di awal dan akhir kegiatan. Keempat, siswa bersyukur atas nikmat dan karunia tuhan yang maha esa. Kelima, siswa berikhtiyar dalam setiap usaha dan berserah diri. Keenam siswa menjaga lingkungan di sekitar sekolah. Ketujuh, siswa memelihara hubungan dengan sesama ciptaan Tuhan. Dan kedelapan, Menghormati orang lain yang menjalankan ibadahnya masing-masing. Hal ini telah sesuai dengan nilai-nilai aswaja an-nahdliyah yang diajarkan di SMK Manbail Futuh. Peneliti selanjutnya dapat meneruskan kajian pada pengukuran sikap spiritual siswa secara kuantitatif sehingga akan melengkapi data tentang sikap spiritual siswa di SMK Manbail Futuh Jenu Tuban. Keywords: Ekstrakurikuler, Kokurikuler, Sikap Spriritual